IMPLEMENTASI KEBIJAKAN RUANG TERBUKA HIJAU KABUPATEN BADUNG DALAM MEMPERTAHANKAN KAWASAN JALUR HIJAU DI KECAMATAN KUTA UTARA - Ary Komala, Luh Nyoman Sinta; Winaya, I Ketut; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2019)
ABSTRACT Green Open Space is an.elongated.area/line.and.clustered, which is an open sapces, where plants grow, both naturally grown and planted. The.purpose.of this research is to.know.how.the.Implementation.Green.Open.Space.Policy of Badung Regency in Maintaining the Green area in North Kuta Sub-District. The policy perfomance was measured by.using.policy.implementation model from Van.Meter.and Van.Horn.with 6 variables that influence policy performance. The results of this research indicate that the implementation of the green open space policy implemented by the Public Works and Spatial Planning Office of Badung Regency still experiences several problems for controlling and spatial planning such as the occurrence of massive function shifts in North Kuta Sub-District and the implementation of sub-optimal regional regulations. Keywords: Implementation, Green Open Space (GOS), Green Areas.